Prognostic value of test(s) for O(6)‐methylguanine–DNA methyltransferase (MGMT) promoter methylation for predicting overall survival in people with glioblastoma treated with temozolomide - McAleenan, Alexandra (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Prognosis). The objectives are as follows: Primary objective The primary objective of this review is to determine which technique (test) for assessing MGMT methylation status best predicts overall survival in people diagnosed with glioblastoma who are treated with temozolomide. We will consider each MGMT test as a separate prognostic factor. See Table 2 for the review question in population, index prognostic factor, comparator prognostic factor(s), outcome, timing, and setting (PICOTS) format. Secondary objective We will undertake a full integrated economic review to identify economic evaluations in relation to the different methods of assessing MGMT methylation status effect on overall survival. Furthermore, we will develop a simple cost‐effectiveness decision model exploring the cost‐effectiveness of alternative approaches to assessing MGMT methylation status. Investigation of sources of heterogeneity If we identify a sufficient number of studies for inclusion, we will examine for each technique/test whether any of the following features is best associated with overall survival. Promoter region/ 5'‐C‐phosphate‐G‐3' (CpG)s analysed (or the antibody used in the case of immunohistochemistry). Cut‐off used (where relevant). Type of tumour sample (FFPE or frozen). We will also investigate the effect of population characteristics including the following. Age. Extent of tumour resection. Karnofsky performance status. IDH status. Recurrent versus first diagnosis. We are assuming constant HRs. To confirm the validity of this assumption we will investigate length of follow‐up as a source of heterogeneity. If studies have started follow‐up for overall survival from different timepoints, we will also investigate this as a source of heterogeneity.